2005
DOI: 10.2307/40204117
|View full text |Cite
|
Sign up to set email alerts
|

Young Soldiers: Why They Choose to Fight

Abstract: The International Labour Office welcomes such applications. The designations employed in ILO publications, which are in conformity with UN practice, and the presentation of material therein do not imply the expression of any opinion whatsoever on the part of the International Labour Office concerning the legal status of any country, area, or territory or of its authorities, or concerning the delimitation of its frontiers. The responsibility for opinions expressed in studies and other contributions rests solely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The database refers to child recruitment facts that occurred between 1981 and 2005 but were prosecuted between 2006 and 2016. 10 While the information registered by the Attorney General's Office was relevant input, this research identified several problems. Firstly, the information was not unified; that is, data on perpetrators and victims were distributed in 19 different matrices.…”
Section: Methodology: Difficulties Of Conducting Research On Child Re...mentioning
confidence: 99%
“…The database refers to child recruitment facts that occurred between 1981 and 2005 but were prosecuted between 2006 and 2016. 10 While the information registered by the Attorney General's Office was relevant input, this research identified several problems. Firstly, the information was not unified; that is, data on perpetrators and victims were distributed in 19 different matrices.…”
Section: Methodology: Difficulties Of Conducting Research On Child Re...mentioning
confidence: 99%
“…22 Findings across the social sciences also indicate the role of social and individual factors in influencing child trajectories into criminal and armed groups, including terrorist groups. Studies have investigated how family and community influence children's trajectories into armed groups 23 as facilitative factors for association 24 or, conversely, protective factors against recruitment. 25 Research also sheds light on the role of community leaders and community practices.…”
Section: Recruitment Patternsmentioning
confidence: 99%
“…Recent literature on youth in post-peace agreement societies note the capacity of youth agency and their possibility for transforming negative discourses that prolong conflict (Boyden, 2003(Boyden, , 2007Alpízar & Bernal, 2003;Alvarado Salgado & Ospina Serna, 2018), their peacebuilding activities and practices (Alvarado, et al, 2012;Özerdem & Podder, 2015), and their ability to absorb and distil nuances from the local culture (Sommers, 2012; Brett & Specht, 2004;Wessells, 2006). This article explores the perceptions and experiences of a group of young university students in Bogotá-Colombia concerning living in the same society with ex-FARC-EP combatants.…”
Section: Leonardo Rafael Luna Eslava Sean Byrnementioning
confidence: 99%